Synergy Between BPKN and Higher Education Institutions in Consumer Protection Education in the Digital Era - Maulidia, Rohmah; Sutopo, Umarwan (El-Barka Journal of Islamic Economics and Business, 2024)
The rise in consumer transactions in the digital era reflects the increasingly complex dynamics of consumer behavior. However, the Consumer Empowerment Index (IKK) in Indonesia remains relatively low, particularly in the higher education sector. This article aims to analyze the role of the National Consumer Protection Agency (BPKN) and higher education institutions in educating and protecting consumers, using the organizational transformation theory as its framework. This research employs a descriptive qualitative method, utilizing primary data collected through in-depth interviews with key figures from BPKN and consumer protection law lecturers, as well as secondary data from official BPKN documents. The findings reveal that although BPKN has implemented several educational programs in select universities, the involvement of State Islamic Higher Education Institutions (PTKIN) remains minimal. The primary obstacles include a lack of synergy, limited resources, and weak implementation of formal collaborations. Recommendations include strengthening consumer protection curricula, expanding strategic collaborations between BPKN and universities, and developing small claims court mechanisms to facilitate consumer access to dispute resolution. This study emphasizes the need for bureaucratic and educational transformation based on synergy to enhance consumer awareness and empowerment in Indonesia.